A theory of democratisation through peace-building. Issue 4 (4th July 2018) - Zürcher, Christoph
Abstract: This contribution presents a theory of democratisation through peace-building. Peace-building is seen as an interactive process between external peace-builders and domestic elites; whether a post-war state develops into a democracy or not depends to a large extent on the outcome of the bargaining process between domestic elites and peace-builders. It is argued that domestic elites typically face many constraints which make adopting democratic reforms a risky and costly proposition. Also, peace-builders usually have much less leverage over domestic elites than one would expect given their resources and man-power. High adoption costs and low leverage explain the outcome of the interaction between peace-builders and domestic elites often results in a peace which is not democratic. The paper uses an analysis of 19 major peace-building missions for exemplifying the theory.